ChemInform Abstract: A Facile, Superacid‐Promoted Sequential Domino One‐Pot Dual C—C Bond Formation and Fischer Indole Synthesis: Rapid Access to 10‐Phenyl‐5, 10‐dihydroindeno[1, 2‐b]indoles. Issue 39 (September 2015) - Reddy, Alavala Gopi Krishna; Satyanarayana, Gedu
Abstract TfOH‐mediated reaction between cinnamic esters (I) and arenes initially furnishes indanones, e.